Comparing three designs of macro-glyphs for poetry visualization - Abdul-Rahman, A; Maguire, E; Chen, M (Eurographics Working Group on Data Visualization, 2014)
Glyphs have been successfully used in poetry visualization for depicting the characteristics and positions of each phonetic articulation in relation to the human vocal system. While existing glyph designs provide visual representations for detailed observation and external memorization of the dynamics throughout a poem, they are less effective for observing the relationship and variance between different lines in a poem and in comparing different poems. In this short paper, we present three designs of macro-glyphs for summarizing the spatio-temporal dynamics at the level of poetic lines. In particular, we use statistics from a collection of poems to guide and optimize the designs. We report our comparative study on the effectiveness of these three designs.